Climate Refugee: Tantangan Bagi Tata Kelola Global - Muhammad Riza Hanafi (Jurnal Transformasi Global, 2015)
AbstractÂ The terminology of Climate refugee is not new. It is somtimed mixed with another concept such as environmental refugee,climate-change refugee, environmental-induced migrant, or climate induced migrant. The concept of environmental refugees itself was introduced for the first time in 1970s and since then it attracted many researcher in the academic community to study it as part of environment/climate change studies. Although academically this phenomenon has been studied by many researchers, however it has not been taken seriously in the policy of global governance. This paper will argue that there are at least three reasons why issue on climate refugees is a challenge to global governance of the 21st century.Â Keywords: climate, environmental, global governance